Disability Studies
VIII, 278 p.
Keywords: Education systems worldwide will only successfully serve the needs of people with disability when we inclusively examine and address disabling issues that currently exist at school level education as well as further and higher education and beyond. The chapters contributing to this edited volume are presented to assist readers with a critical examination of contemporary practice and offer a concerted response to improving inclusive education. The chapters address a range of important topics related to the field of critical disability studies in education and include sections dedicated to Schools, Higher Education, Family and Community and Theorising. The contributors entered into discussions during the 2014 AERA Special Interest Group annual meeting hosted by Victoria University in Australia. The perspectives offered here include academic, practitioner, student and parent with contributions from Australia, New Zealand, Nigeria, the UK and the US, providing transnational interest. This book will appeal to readers who are interested in innovative theoretical approaches, practical applications and personal narratives. The book is accessible for scholars and students in disciplines including education, sociology, psychology, social work, youth studies, as well as public and allied health. The Introduction by Professor Roger Slee (The Victoria Institute, Victoria University, Australia) and Afterword by Professor David Connor (City University of New York) provide insightful and important commentary. Cover photograph by Paul Dunn and design by Hendrik Jacobs.